Narrativas sobre la depresión en las personas mayores de 60 años que pertenecen a la Unidad Social en Choachí- Cundinamarca (2023)
The objective of this study is to describe the narratives about depression in people over 60 years of age who belong to the Unidad Social San Luis María de Montfort shelter in ChoachíCundinamarca. In this way, different specific objectives are articulated; firstly, explore the aspects related to the ideas of death present in the elderly about depression; secondly, to identify depressive symptoms in the history of the elderly and finally, to analyze the aspects related to the support network or mutual support in emotional situations among the elderly who live in the San Luis María de Montfort Social Unit in Choachí -Cundinamarca.